Methylthioadenosine phosphorylase deficiency in tumors: A compelling therapeutic target - Fan, Na; Zhang, Yi; Zou, Suyun (Frontiers in Cell and Developmental Biology, 2023)
The methionine salvage pathway is responsible for recycling sulfur-containing metabolites to methionine. This salvage pathway has been found to be implicated in cell apoptosis, proliferation, differentiation and inflammatory response. Methylthioadenosine phosphorylase (MTAP) catalyzes the reversible phosphorolysis of 5′-methylthioadenosine, a by-product produced from polyamine biosynthesis. The MTAP gene is located adjacent to the cyclin-dependent kinase inhibitor 2A gene and co-deletes with CDKN2A in nearly 15% of tumors. Moreover, MTAP-deleted tumor cells exhibit greater sensitivity to methionine depletion and to the inhibitors of purine synthesis. In this review, we first summarized the molecular structure and expression of MTAP in tumors. Furthermore, we discussed PRMT5 and MAT2A as a potential vulnerability for MTAP-deleted tumors. The complex and dynamic role of MTAP in diverse malignancies has also been discussed. Finally, we demonstrated the implications for the treatment of MTAP-deleted tumors.